Comparison Of Harmonic Balance And Multiple Scale Method On Degree Of Nonlinearity For Duffing Oscillator - Low, Pei Sing; Ramlan, Roszaidi; Muhammad, N.S; Ghani, H. A. (Asian Research Publishing Network (ARPN), 2016)
-